2014
DOI: 10.3844/ajptsp.2014.1.12
|View full text |Cite
|
Sign up to set email alerts
|

HYPOGLYCEMIC, HEPATO-RENAL AND ANTIOXIDANT POTENTIAL EFFECTS OF <i>CHAMOMILE</i> RECUTITA FLOWERS ETHANOLIC EXTRACT IN STREPTOZOTOCIN-DIABETIC RATS

Abstract: This study was undertaken to evaluate the hypoglycemic and hepatorenal protective effect of ethanolic extract of Chamomile recutita flowers in streptozotocin-Diabetic Rats. Before the beginning of the experiments, acute and subacute studies were carried out in control animals first to investigate the LD50 of this extract. In the experimental design, adult male albino rats were divided into five groups: (1) normal control, (2) control + extract, (3) diabetic control, (4) diabetic+extract and (5) diabetic+gliben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This appeared from the amelioration of MDA to near normal level and the significant improvement of the GSH and TAC contents. These results agree with that reported for chamomile flowers extract [48,49] and for fennel seeds extract. [16,50] In addition, chamomile flower and fennel seed extract could also significantly decrease serum ALT, AST, and ALP, suggesting their hepatoprotective activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This appeared from the amelioration of MDA to near normal level and the significant improvement of the GSH and TAC contents. These results agree with that reported for chamomile flowers extract [48,49] and for fennel seeds extract. [16,50] In addition, chamomile flower and fennel seed extract could also significantly decrease serum ALT, AST, and ALP, suggesting their hepatoprotective activity.…”
Section: Discussionsupporting
confidence: 93%
“…Polyphenols and flavonoids in chamomile flowers extracts and apigenin-7-O-glucoside as the major constituent of chamomile which inhibited cancer cell growth were recorded. [60] Al-Musa and Al-Hashem [49] reported that the administration of ethanolic extract of chamomile flowers to streptozotocin-induced diabetic rats significantly ameliorated the morphological changes in the livers of treated rats. They attributed these effects to its potent antioxidant potential resulting in membrane stability.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies revealed several physiological responses to tea, which may have a significant effect on the prevention, management and treatment of certain chronic diseases . The effects of these teas have been demonstrated in, for example, chamomile tea (500 mg kg −1 for 20 days), which has recently been shown to have a hypoglycaemic effect by causing a significant decrease in the serum glucose levels of both diabetic and non‐diabetic patients …”
Section: Synergistic Effect Of Combinations Of Herbal Teas On Diseasementioning
confidence: 99%
“…34,35,87 The effects of these teas have been demonstrated in, for example, chamomile tea (500 mg kg −1 for 20 days), which has recently been shown to have a hypoglycaemic effect by causing a significant decrease in the serum glucose levels of both diabetic and non-diabetic patients. 88 On the contrary, herbal teas such as sage (Salvia officinalis), peppermint, thyme (Thymus vulgaris), absinthium (Artemisia absinthium), roselle, olive leaves (Olea europaea), shrubby blackberry (Rubus fruticosus) relax tea (Hypericum perforatum; a commercial brand containing St. John's Wort, Melissa (Melissa officinalis), garden valerian (Valeriana officinalis), sweet fennel (Foeniculum vulgare) and lavender (Lavandula angustifolia) which have generally been used for the treatment of diabetes did not show any in vitro inhibitory effects on glucose absorption. 27 However, they could contribute to the maintenance of plasma antioxidant levels.…”
Section: Synergistic Effect Of Combinations Of Herbal Teas On Diseasementioning
confidence: 99%
“…Although the mechanism of IR development not yet exactly known, it has been established that chronic inflammation in key metabolic tissues, including the liver due to fat accumulation is an important pathogenic factor in IR development (Bashir et al, 2014). Hepatic and systemic inflammatory cytokines produced in obesity activate intracellular kinases which capable to inhibit key elements of insulin signaling pathway with subsequent development of insulin resistance (Al-Musa and AL-Hashem, 2014). Tumor Necrosis Factor-α (TNF-α) and Interleukin-6 (IL-6) among several hepatic cytokines are playing an essential role in hepatic inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%